Partisipasi Pemilih dalam Pemilihan Umum Bupati/Wakil Bupati Langkat Tahun 2018 - Suhardi Suhardi; Muhammad Arif Nasution; Heri Kusmanto (Universitas Negeri Medan, 2019)
This study describes the participation of voters in regional head elections. The form of research used is descriptive qualitative method. The researcher conducted research directly at the Langkat Regency General Election Commission and the people who became voters in the simultaneous Regional Head General Elections especially the Langkat Regent and Deputy Regent General Elections in 2018. The informants in this study were the Langkat Regency General Election Commissioner. The main informants were the Voters namely the Langkat Regency Population who were at least 17 years and above. Primary data collection, carried out by interview and observation. Secondary data collection is done by library research. The methods of data analysis in this study are as follows: Data Collection, Data Reduction, Data Presentation and Conclusion Withdrawal of Research Results: The level of voter participation in the Election of Regional Heads (Case Study of Election of Regent and Deputy Regent of Langkat in 2018) which holds 2019- 2024 is 66.48% (or is in the Medium category). Kuala Subdistrict (89.99%) is the highest percentage of voter participation in polling stations in the Langkat District and Deputy Regent Election, while Pangkalan Susu District is the lowest at 55.25%.